Pricing risky bank loans in the new Basel II environment - Iftekhar Hasan; Cristiano Zazzara (Bank of Finland, 2006)
Recently, banking literature has had a quest for appropriate pricing of bank loans under the new Basel II rules and has been in pursuit of possible outcomes for undertaking such credit risk.In this paper, we propose a simplified formula to price bank's corporate loans, aiming at making bank managers aware of the creation/destruction of shareholder value.We show that the mathematical treatability of the proposed formula and its easy feeding with internal and market inputs allow simple implementation by the final user.
URN:NBN:fi:bof-20140807542
Keywords: C63; G12; G21; G28; 330; Basel II; rating; pricing; exposure at default; EVA